2021
DOI: 10.1089/whr.2020.0117
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Breast Cancer Diagnosis and Treatment Among Women in Ghana: A Qualitative Study

Abstract: Background: Breast cancer is the leading cause of cancer death among Ghanaian women and most women are identified once they develop symptoms. Women then must navigate a complex health care system to get diagnosed and receive orthodox medicine. We describe Ghanaian women's pathways of care from breast cancer-related symptom detection to treatment receipt. Methods: We conducted a qualitative study using an empirical phenomenological approach. We used a purposive sampling technique to recruit 31 women with breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…This assertion is confirmed by previous studies [10,12]. The mean age observed in our patients was comparable to data from similar breast cancer patients' population across Ghana [17,18]. Also consistent with our findings, Dedey et al [17] and Mburu et al [18] reported that majority of breast cancer patients subscribed to the national health insurance scheme (89% & 97% respectively), which is at variance with the estimated national enrollment figure for women (66%) [19].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This assertion is confirmed by previous studies [10,12]. The mean age observed in our patients was comparable to data from similar breast cancer patients' population across Ghana [17,18]. Also consistent with our findings, Dedey et al [17] and Mburu et al [18] reported that majority of breast cancer patients subscribed to the national health insurance scheme (89% & 97% respectively), which is at variance with the estimated national enrollment figure for women (66%) [19].…”
Section: Discussionsupporting
confidence: 92%
“…The mean age observed in our patients was comparable to data from similar breast cancer patients' population across Ghana [17,18]. Also consistent with our findings, Dedey et al [17] and Mburu et al [18] reported that majority of breast cancer patients subscribed to the national health insurance scheme (89% & 97% respectively), which is at variance with the estimated national enrollment figure for women (66%) [19]. Amoako et al [20] reported on summarized data from the Kumasi Cancer Registry and found that breast cancer accounted for 30% of all female cancers and was the leading cause of cancer in the Kumasi metropolis of Ghana.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Most indicators focused on breast cancer management from referral to follow-up. This is supported by Mburu and his colleagues that management of breast cancer requires a holistic approach consisting of early detection, diagnosis through treatment, consistent follow-ups and review (32).…”
Section: Discussionmentioning
confidence: 92%
“… 3 8 23 31 36 44–46 Some women sought over the counter medications for pain management. 37 Seeking assistance from someone other than a nurse or doctor was associated with a larger mass at diagnosis for breast cancer, which could include a diverse mix of pluralist and community supports. 44 Some health professionals also advised herbal alternatives, delaying medical cancer treatment.…”
Section: Resultsmentioning
confidence: 99%